Clinical aspects and laboratory iron metabolism, anemias : concepts in the anemias of malignancies and renal and rheumatoid diseases - Wick, M. (Manfred) (Springer, 2011)
Iron is essential for most forms of life, including humans. On the other hand, iron is also potentially toxic. Therefore, the control of iron metabolism and maintenance of iron hemostasis is an crucial part of many aspects of human health and disease. This booklet is designed for physicians, clinical lab personnel and medical students.